Relación de los instrumentos de evaluación y el aprendizaje de actitudes ecológicas en los alumnos del 2do grado de secundaria en las I.E Monterrey, Santa Isabel - Ventura Ramos, German (2013)
The improvement of the quality of the learning in both the many attention of our educational system's actors has monopolized last decades in our country. In front of this level superior- spheres situation, it has happened to me that it has appealed, as always, to the temporary recipes insert elaborate starting from leavings of partial successes in another latitudes of the planet in his viability's fictitious veil wrapped. As usual, the rulers choose inserting short-lived liquid solutions from up and they refuse still to receive that he finds to the educational quality's improvement more direct manner in the daily monitored dynamics of the lecture halls for the teachers, constantly warring characters to this challenging reality and because they are the actors of better preparation to find them solution to the complexities of the formation of the human being on the basis of solid learning's. The mistaken solutions insert is aggravating to the educational quality's · improvement more and more the process's readdressing teaching learning in everyone them areas; The educational area environmental he is not the odd man out, furthermore when at present the requirements of reverting the conduct of the consumption and the human being's contaminant is made more urgent. This is shown in the environmental- deterioration increment of our planet. One of the crucial points in order to the improvement of the student's performance is to opera te on the evaluation's. products, first trying to making suitable instruments to the measured variable's characteristics and next having an effect on the said- characteristics strengthening. Knowing that the show metacognitiva of the evaluation from the learning's autoconscience the same pupil will propitiate his achievement's more and more autonomous self-regulation. No less important the diagnostic show, that he provides information in order to decision makings on the diversity of potential, is interests, capabilities and achievement levels existent in the classroom. The diagnostic show he can take as person giving a reference aftermaths as point of start in a pedagogic intervention. In that connection the attitudes evaluation, once was understood at the present time as a fact-finding process of the didactic action, he loses the character or the qualification purpose, to become converted in information instrument of the tuitional process and learning. For that reason we focus in the associated scrutinizing of this dimension's evaluation according to custom of the best-suited instruments. lnvestigation came true in the second institutional grade educational of the secondary level Santa Isabel and Monterrey of the jurisdiction of Nueva Cajamarca's district for the sake of verifying the possible association among two variables of qualitative nature, the first: The application of the evaluation instruments of the ecological attitudes as inherent task to the teaching work and the learning of the ecological attitudes as achievements in the pupils seconds her. The learning's the attitudes, once was interpreted as much as process turns theoretic sustenance about the conception and as product through all his measurability, in addition to his configuration in the thematic axle educational environmental. analysis incórporates For other of the process evaluation including procedures and the related instruments to the manifestation's measurement the student's the attitudes. Our objective attended to attain the more obvious interpretation of the possible association among the application of the evaluation instruments and the educational learning of the ecological attitudes in the pupils of the secondary level's second institutional grade Santa Isabel and Monterrey of Nueva Cajamarca's district turning to 7 teachers and to 86 pupils as members of the population in order to each subjects group.